Demonstration Technology Application and Analysis on the Scientific and Technological Progress - Qingzhu Qi; Zhixiao Jiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper takes Tianjin for example and analyzes the development tend of scientific and technological progress in Tianjin. From five aspects as ‘environment of scientific and technological progress’, ‘input of scientific and technological activities’, ‘output of scientific and technological activities’, ‘high-tech industrialization’, ‘science and technology for economic and social development’, the paper analysis the correlation between GDP and scientific and technological progress. Research finding shows that these five indicators are all positive correlated with the GDP, and especially ‘environment of scientific and technological progress’, ‘input of scientific and technological activities’, and ‘science and technology for economic and social development’, which are significantly positive correlation of GDP. The extent to which these five indicators impact the GDP from strong to weak is ‘input of scientific and technological activities’, ‘science and technology for economic and social development’, ‘environment of scientific and technological progress’, ‘high-tech industrialization’, and ‘output of scientific and technological activities’. The ‘input of scientific and technological activities’ index (2011) in Tianjin scores only 70 which ranks fourth among the five indexes, however its impact on GDP is most significant. So it would be best for Tianjin to increase the human and financial input in ‘scientific and technological activities’ to promote the growth of GDP in future. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3129